At-Tarbiyah Al-Qiyadiyyah Al-Islamiyah fi Al-Ma‘Ahid Al-Islamiyyah bi Indonesia Wifqa Manzhuri Thariq As-Suwaidan - Abd. Rohim; Endin Mujahidin; Didin Saefuddin; Adian Husaini (el Harakah: Jurnal Budaya Islam, 2017)
توصل الباحث من هذه الدراسة إلى استنتاج وهو أن مفهوم التربية القيادية لطارق السويدان تربوي، وتدريبي، وواقعي، وأسوتي، وإسلامي، بمعنى أن تشكيل قائد هو من خلال التعليم والتدريب ووفق الواقع، وليكون نموذجا، وبالمعايير الإسلامية، وأن مفهوم التربية القيادية لطارق السويدان هو تعزيز نظرية وارن بلانك باسم "108 مهارات قيادية طبيعية" وهي النظرية التي أكدت على أنه لا يوجد شخص ولد قائدا في شكل طبيعي، لأن القيادة هي مجموعة من الخصائص والمهارات التي يمكن تعلُّمها، وأن تطبيق مفهوم التربية القيادية لطارق السويدان في إندونيسيا هو باسم "برنامج تعليم وتدريب الشباب القيادة الإسلامية 30 ساعة"، والتطبيقات للتربية القيادية الإسلامية وفق منظور طارق السويدان هي برنامج التعليم والتدريب القيادي الذي يُقدَّم للشباب الذين هم من أشد الموارد البشرية خصبة، خطوة خطوة، في مؤسسة أو دورة تدريبية أنشئت خاصة بهذا الغرض، وذلك باستخدام مختلف أساليب التعليم والتدريب المتنوعة، وأن مثل هذا التعليم حدث ولا يزال يحدث في واقع المجتمع الإندونيسي مما يؤكد على أهمية دور الكيايات (الشيوخ) في البسانترينات (المعاهد الإسلامية) في إعداد كوادر العلماء الذين هم قادة للمستقبل. The conclusion of this research is that the concept of leadership education of Thariq as-Suwaidan is the concept of leadership education that having the characteristic of tarbawi, tadribi, waqi‘iy, uswati and Islami. In the sense of the formation of a leader must be through education, training, reality, model, and Islamic. Thariq as-Suwaidan’s Leadership Concept is to strengthen Warren Blank’s theory by the name of “108 Skills of Natural Born Leaders”, the theory that there is no natural leader. Leadership is a collection of traits and skills that can be learned. Application of Thariq as-Suwaidan Leadership Education Concept in Indonesia is under the name of “Youth Leadership Education Training Program 30 Hours”. The application of Islamic leadership education of Thariq as-Suwaidan is a leadership and leadership training program provided to the youngest of the most fertile human resources, step by step, in a training institute or course established specifically for this purpose, using various varied learning methods. The kind of education has really happened and will constantly happen in the reality of Indonesian society. The condition strictly shows the importance of the roles of Islamic scholars (ulama) in Islamic schools or Islamic institutions to perform and to shape their next generation to become the future leaders.